SUCROSE IN DETOXIFICATION OF COFFEE PLANTS WITH GLYPHOSATE DRIFT - Alecrim, Ademilson de Oliveira; Guimarães, Rubens José; Castanheira, Dalyse Toledo; Rezende, Tiago Teruel; de Figueiredo Carvalho, Milene Alves; Voltolini, Giovani Belutti (Coffee Science - ISSN 1984-3909, 2019)
The weed’ control in coffee plants has great importance, as they compete for light, water and nutrients. The chemical control is the most used, emphasizing the glyphosate, however, when applied, drift can occur and consequently cause injuries to coffee. Many farmers use the sucrose application with the objective to reverse the damage caused by the herbicide drift, even without scientific basis to justify such action. The objective of this study was to evaluate the effect of the sucrose application on the detoxification of coffee plants in the implantation phase with glyphosate drift. The experiment was conducted in a greenhouse, using a randomized block design, arranged in a 3 x 3 factorial scheme with 2 additional treatments, using 3 sucrose doses (2, 4 and 8%) with 3 application times (1, 24 and 168 hours after intoxication with 10% of the commercial glyphosate dose) with an additional one in which the plants were not intoxicated and not treated with sucrose and the other additional only with plants intoxicated by glyphosate. After 75 days conducting the experiment, growth, physiological and anatomical characteristics were evaluated. The application of sucrose in the reversal of intoxication of growth variables (height, leaf areaThe objective of this study was to evaluate the effect of the sucrose application on the detoxification of coffee plants in the implantation phase with glyphosate drift. number of leaves, shoot dry weight and dry weight of the root system) was not efficient. For the physiological variables the application of 2% sucrose, one hour after glyphosate intoxication was the most efficient treatment.